Study on the extraction, antioxidant and prebiotic activity of the polysaccharides from the fruits of Phyllanthus emblica L. - Huang, Haotian; Zhou, Xiaobo; Sun, Mengge; Chen, Jiajie; Tan, Tao; Yang, Dongsheng (Frontiers in Nutrition, 2025)
IntroductionPolysaccharides extracted from the fruits of Phyllanthus emblica L. (PEP) have demonstrated various bioactivities, including antioxidant and prebiotic effects. This study aimed to optimize the extraction of PEP using ultrasonic microwave synergistic extraction (UMSE) and evaluate its bioactivities.MethodsThe UMSE process was optimized using response surface methodology (RSM) to identify the most efficient extraction conditions. Antioxidant capacity was evaluated through DPPH, ABTS, and hydroxyl radical scavenging assays, alongside total reducing capacity measurements. For prebiotic activity, the ability of PEP to promote the growth of Lactobacillus casei, Lactobacillus acidophilus, and Lactobacillus plantarum was compared with that of standard prebiotics. Changes in pH and lactic acid production in the culture medium were also monitored.ResultsOptimal UMSE parameters included microwave power (370 W), ultrasonic power (340 W), extraction time (25 minutes), and a solid-liquid ratio of 1:6.5 g/mL. These conditions achieved an extraction yield of 8.09%, aligning with the predicted value. The UMSE method showed higher extraction efficiency and sugar content compared to traditional water extraction, with a reduction in impurities. The extracted PEPs exhibited significant scavenging activity against DPPH, ABTS, and hydroxyl radicals, as well as robust total reducing capacity. Additionally, the PEPs demonstrated resistance to hydrolysis by artificial saliva and gastric juice, suggesting their ability to reach the gastrointestinal tract intact. In prebiotic assays, PEP (UMSE-derived, PEP-U) stimulated the proliferation of Lactobacillus spp. more effectively than water-extracted PEP (PEP-W), correlating with increased lactic acid production and reduced pH in the culture medium.DiscussionThese results highlight the dual bioactivity of PEP as both an antioxidant and prebiotic, suggesting its potential as a functional food ingredient for promoting gut health and oxidative balance.